2014
DOI: 10.1021/am504779t
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Nanocarrier Fortified with a Dipyridinium-Based Amphiphile for Eradication of Biofilm

Abstract: Annihilation of bacterial biofilms is challenging owing to their formidable resistance to therapeutic antibiotics and thus there is a constant demand for development of potent antibiofilm agents that can abolish established biofilms. In the present study, the activity of a dipyridinium-based cationic amphiphile (compound 1) against established bacterial biofilms and the subsequent development of a compound 1-loaded nanocarrier for potential antibiofilm therapy are highlighted. Solution-based assays and microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 58 publications
0
53
0
Order By: Relevance
“…18 Engineering nanomaterials provides a potential platform to prevent payload degradation and to tune molecular interactions with bacteria. 19,20,21,22 Previous reports have shown that encapsulating essential oils into surfactant-stabilized colloidal delivery vehicles improves their aqueous stability and increases the antimicrobial activity of small molecule payloads. 23,24,25 However, these carriers often induce adverse hemolytic or irritating effects restricting their compatibility with biological tissues.…”
mentioning
confidence: 99%
“…18 Engineering nanomaterials provides a potential platform to prevent payload degradation and to tune molecular interactions with bacteria. 19,20,21,22 Previous reports have shown that encapsulating essential oils into surfactant-stabilized colloidal delivery vehicles improves their aqueous stability and increases the antimicrobial activity of small molecule payloads. 23,24,25 However, these carriers often induce adverse hemolytic or irritating effects restricting their compatibility with biological tissues.…”
mentioning
confidence: 99%
“…The wells were air‐dried for 45 min. The formation of the biofilm was then ascertained by fluorescence microscopy in separate sets by cFDA‐SE and CR staining by a standard procedure . In a separate experiment, biofilm imaging was also carried out by tracking the inherent fluorescence of C4.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate experiment, S. aureus MTCC 96 biofilm growth in control samples (devoid of C4) and in the presence of C4 was ascertained by FESEM analysis by a previously described method . In the metal supplementation experiments with C4, S. aureus MTCC 96 biofilm was grown in a sterile 96‐well microtiter plate in BHI medium containing glucose (0.25 %) and varying concentrations of C4 (10–320 μ m ).…”
Section: Methodsmentioning
confidence: 99%
“…HNPs were initially generated by following a previously described desolvation method . To generate C1‐loaded HSA nanocarrier (C1‐HNC), HNPs (1.0 mg mL −1 in sterile MilliQ water, pH titrated to 8.2) were interacted overnight with varying concentrations of C1 (10–400 μ m ) on a rocker at room temperature.…”
Section: Methodsmentioning
confidence: 99%